Some New Results of Weakly Contractive Mappings in Gb -Metric Space - Gupta, Vishal; Saini, Rajani; Saeed Khan, Mohammad (Science & Technology Asia, 2021)
In our present work, we prove some generalized weakly contractive mappings results in Gb - metric space. These outcomes extend, unify and develop the available results in literature. We also provide some corollaries and examples to show the novelty and usefulness of outcomes.